1987
DOI: 10.1203/00006450-198706000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Theophylline on Regional Cerebral Blood Flow Responses to Hypoxia in Newborn Piglets

Abstract: ABSTRACT. Theophylline attenuates cerebral hypoxic hyperemia in several adult models and this is thought to be due to receptor-mediated antagonism of adenosine, a proposed mediator of hypoxic hyperemia. This attenuation of hypoxic hyperemia reduces cerebral oxygen delivery and mav thus ieo~ardize cerebral oxidative metabolism. With these con~de~ations in mind, and because theophylline is widely used in neonatal medicine, the present study was designed to investigate the effect of theophylline on regional cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
2
9
2
Order By: Relevance
“…On the contrary, using the newborn piglet un der conditions of controlled ventilation to maintain a constant Pco2> Stonestreet et al [5] showed that a therapeutic dose of ami nophylline (6 mg/kg) did not alter CBF. McPhee and Maxwell [8] confirmed these findings with theophylline (10 mg/kg) in the same animal model.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the contrary, using the newborn piglet un der conditions of controlled ventilation to maintain a constant Pco2> Stonestreet et al [5] showed that a therapeutic dose of ami nophylline (6 mg/kg) did not alter CBF. McPhee and Maxwell [8] confirmed these findings with theophylline (10 mg/kg) in the same animal model.…”
Section: Discussionsupporting
confidence: 71%
“…CBF was measured with either the xenon-133 inhala tion technique, or the xenon-133 intracarot id injection method [6,7]. In contrast to adults, Stonestreet et al [5] and McPhee and Maxwell [8] found no effect of aminophyl line and theophylline, respectively, on CBF (measured by microspheres) in the newborn animal.…”
Section: Introductionmentioning
confidence: 99%
“…These results apparently differ from previously studies that found that aminophylline [4,[6][7][8][9] and theophylline [5] significantly reduce CBF [5,[7][8][9] and CBF velocity [4,6]. Nonetheless, the study design of these papers is very different from ours: (1) loading doses of aminophylline (or theophylline) were administered to the patients; (2) some studies evaluated CBF [5,[7][8][9] and others evaluated CBF velocity [4,6]; (3) some studies were performed by cerebral Doppler ultrasounds [4,6], others by xenon clearance technique [5,7], or by NIRS [8,9]; (4) none of them provided continuous monitoring of cerebral hemodynamics that was able to show transient and slight changes, and (5) there is wide variability in the study period. In particular, Bucher et al [9] applied NIRS from 10 min before to 20 min after administration of aminophylline, while in the remaining studies data collection started 60 min after drug administration or later, and none of them investigated possible changes during this initial unrecorded period.…”
Section: Discussioncontrasting
confidence: 56%
“…In new born pigs, for instance, hypoxia increased brain in terstitial fluid adenosine concentration (Park et ai. , 1987), but hypoxia-induced hyperemia was not di minished by theophylline (McPhee and Maxwell, 1987). Similar differences concerning the role of prostaglandins in hypoxia-induced cerebrovasodila tion have also been noted.…”
Section: Discussionsupporting
confidence: 53%